Cadmium monitoring in saliva and urine as indicator of smoking addiction - Talio, María Carolina (2010)
Cadmium is one of the many substances that may be acquired through active and passive smoking of tobacco. Saliva and urine are proposed for cadmium monitoring of non-smokers, second hand smokers, smokers and tobacco chewing appertaining to San Luis citizens without occupational exposition. Biological samples were collected by the same subjects, under strict proceeding instructions of sampling. Physical characteristics of samples were observed and checked with commercial test. Samples were analyzed using an adapted molecular fluorescence methodology with a previous extraction step. Stability of biological samples was daily studied for a period of one month. The method was successfully validated for accuracy, precision, linearity, specificity, and sensitivity. The simplicity and low coefficient of variance confirm the suitability of the method for urinary and salivary cadmium analyses. On the other side, the obtained results are in concordance with previous national epidemiological dates.